Evaluasi Implementasi Manajemen Stratejik Dengan Menggunakan Manajemen Berdasarkan Tujuan (MBO) Pada PT Beta Medical Sebagai Perusahaan Alat Kesehatan - Affar, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the results of the evaluation of the implementation of strategies that have been implemented so far using Management by Objectif (MBO). This research was conducted at PT Beta Medical as a Medical Device Company in Indonesia. MBO is used in this study as an analytical tool because this company is a family company and this company is not so complex and not large-scale, only being the sole and non-single distributor of medical devices imported from the manufacturing countries. So to achieve this goal, this study uses a descriptive qualitative approach. Data collection techniques were carried out through interviews, observations, and documentation studies. Data analysis procedures are data reduction, data display, and verification. While the research subject is Mr. Andre Marthino, B.Mgt, MIB as the Marketing Director at PT Beta Medical and also as the son of the owner of the company PT Beta Medical, namely Mr. Drs. Ec. Amiruddin M. Noer, MBA. The results of this study indicate that the implementation of the strategy that has been implemented by PT Beta Medical is still very ineffective because the targets set by the company have not been achieved for the last two years. Most likely in the following year it will not be achieved. All of this can happen because the implementation process is not so good, clear and focused on each division which results in many obstacles and problems faced by the company.